The Pretension Design of Cable Mesh considering the Large Deformation of Ring Truss - Hu Jianfeng; Wang Lipeng; Yang Jungang (International Journal of Aerospace Engineering)
The conventional pretension design of cable mesh usually takes the ring truss as a rigid body or assumes small deformation. This method needs to be more accurate in designing super large aperture antennas. A cable mesh design method considering the large deformation of the ring truss is proposed in this paper based on the flexible multibody dynamics (FMD) and the force density method (FDM). With this method, the significant range deviation of the boundary points’ position of the ring truss under the tension of the external area of the cable mesh after the completion of the pretension design can be predicted with high accuracy. After the ring truss and cable mesh surface are assembled stably, there is only a minimal deviation between the actual mesh surface and the theoretical mesh surface of the antenna, and there is only a minimal deviation between the genuine mesh pretension and the design pretension. The above calculation method is verified by numerical simulation, and the simulation results show that the technique can be applied to the mesh pretension design of a super large aperture ring deployable antenna.